The Effectiveness of Guess Tool Game to Teach Vocabulary to the Eighth Grade Students at MTs Negeri in OKU Timur - Zulaikah Zulaikah; Yunawati Yunawati (Universitas Nurul Huda, 2018)
This article was experimental research, entitled “The Effectiveness of Guess the Tool Game to Teach Vocabulary to the Eighth Students at MTs Negeri in OKU Timur”. The writer used true experimental design. The objective this study was “to find out whether Guess the Tool Game is effective or not to teach vocabulary to the Eighth Grade Students’ at MTs Negeri in OKU Timur. The Populations were all eighth-grade students at MTs Negeri in OKU Timur with total number of 165 Students. The samples were class VIII.1 and class VIII.3. It divided into two class, experimental class and control class. The sample of this research was taken by using cluster random sampling. And independent t-test used for analyzing the data. Based on result analysis, t-obtained mean differences between post-test of experimental class and post-test of control class. From the analyzing the data, and obtained the t-obtained was higher than critical value of t-table. For t-obtained 4.83 and t-table was 1.999. Therefore, the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It meant that the use of Guess the Tool Game was effective to teach vocabulary to the eighth-grade students at MTs Negeri in OKU Timur.